2022
DOI: 10.1080/10717544.2022.2118398
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary delivery of favipiravir inhalation solution for COVID-19 treatment: in vitro characterization, stability, in vitro cytotoxicity, and antiviral activity using real time cell analysis

Abstract: Favipiravir, an RNA-dependent RNA polymerase (RdRp) inhibitor, is used to treat patients infected with influenza virus and most recently with SARS-CoV-2. However, poor accumulation of favipiravir in lung tissue following oral administration has required an alternative method of administration that directly targets the lungs. In this study, an inhalation solution of favipiravir at a concentration of 2 mg mL −1 was developed and characterized for the first time. The chemical stability of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Moreover, soft-mist inhalers provide superiority with their easy use, patient-based dose setting and closed mouthpiece technology that prevents the spread out of contaminated aerosol droplets [60,63,64], making it advantageous for their use in the pulmonary infectious diseases. In our previous study performed to evaluate the in vitro antiviral activity of favipiravir, it was concluded that favipiravir at a dosage of 2 mg/mL effectively inhibits the SARS-CoV-2 virus [33]. The follow-up preclinical data support the claim of the study that the inhalation route provides higher lung accumulation compared to plasma.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, soft-mist inhalers provide superiority with their easy use, patient-based dose setting and closed mouthpiece technology that prevents the spread out of contaminated aerosol droplets [60,63,64], making it advantageous for their use in the pulmonary infectious diseases. In our previous study performed to evaluate the in vitro antiviral activity of favipiravir, it was concluded that favipiravir at a dosage of 2 mg/mL effectively inhibits the SARS-CoV-2 virus [33]. The follow-up preclinical data support the claim of the study that the inhalation route provides higher lung accumulation compared to plasma.…”
Section: Discussionmentioning
confidence: 68%
“…Secondly, the translation from human inhalation dose to rat inhalation dose was scaled as mentioned by Nair and Jacob [32]. Moreover, we recently reported that favipiravir exerts antiviral activity at the concentrations between 0.25 and 3 mg/mL on Vero-E6 that were infected with SARS-CoV-2/B.1.36 [33]. Then, the dosage was prepared in the appropriate volume to fill the dead space in the device and to reach approximately 50% accumulation in the lungs [34].…”
Section: Experimental Designmentioning
confidence: 99%
“…reported that favipiravir inhalation solution in PBS buffer is stable for over a year when stored at the refrigerated condition [ 56 ]. The authors also found that nebulisation of 2 mg/mL favipiravir is optimal to achieve both antiviral and minimal toxicity in Vero-EG infected cells and Calu-3 lung epithelial cells, respectively [ 56 ]. A favipiravir solid lipid nanoparticle formulation for inhalation was developed with promising aerosolisation and antiviral properties [ 8 ].…”
Section: Inhalation Nanotherapies For Viral Respiratory Infectionsmentioning
confidence: 99%
“…Some adverse effects were noted with FPV such as diarrhea, changes in liver function parameters and hyperuricemia 7 . Accordingly, new dosage forms are being formulated for administration of FPV through lung inhalation 8 . Furthermore, there is an increasing need to formulate oral solution dosage forms suitable for children use 9 .…”
Section: Introductionmentioning
confidence: 99%